PENGEMBANGAN MODUL BERBASIS KEARIFAN LOKAL TERINTEGRASI PROFIL PELAJAR PANCASILA PADA MATA PELAJARAN IPAS MATERI ENERGI KELAS IV DI SDN KLIWONAN - Asa Faedah; Nur Ngazizah; Suyoto (LPPM STKIP Bina Bangsa Meulaboh, 2024)
The problem of this research is based on problems, namely the teaching materials used are not yet varied, students do not have handbooks, local wisdom and the Pancasila student profile have not been applied in learning activities. This research aims to: 1) Produce a product in the form of a local wisdom-based module integrated with the profile of Pancasila students in the class IV science and energy subject at SDN Kliwonan. 2) Knowing the feasibility of the module being developed. The type of research used is research and development or (Research and Development) with a 4D model (Define, Design, Develop and Disseminate). The subjects of this research were 30 class IV students at SDN Kliwonan. Data collection techniques are observation, interviews, questionnaires, documentation and tests. The instruments used were validation questionnaires for material experts, media experts and teachers, student responses, learning implementation observation sheets, Pancasila student profile attitude observation sheets as well as pretest and posttest questions. The results of the research show that: 1) A module product based on local wisdom integrated with the profile of Pancasila students in the class IV energy science and science subject at SDN Kliwonan was produced with a 4D model. 2) The feasibility of the module in the validity aspect obtained a percentage of material experts of 96%, media experts of 85%. , and teachers, namely 95.60% very valid category. The practical aspect of the module from assessing student responses in limited trials was 95% and extensive trials was 93.95%. The results of learning implementation from observer I were 95% and observer II was 93%. The average percentage is 94%. The results of the practicality aspect obtained very practical criteria. The effectiveness aspect is based on the results of comparing the pretest and posttest scores, obtaining a Gain Score of 0.6 in the effective category. The results of the assessment of the Pancasila student profile attitude observation sheet in the 6 aspects were > 2.50, very effective. Based on the results above, this module is declared feasible.